College Students’ Perceptions of Influenza Vaccination and Childhood Immunizations (International Journal of Studies in Nursing, 2019)
Background: After reviewing the literature on flu vaccinations and childhood immunizations, it was concluded that participation in these preventative measures is beneficial to health in increasing the chances of protection from specific diseases. Further studies show that not all college students receive them or plan to have their prospective children vaccinated. Purpose: The purpose of this study was to determine college students’ perception of influenza vaccination and childhood immunizations. Method: This was a quantitative, non-experimental study with a descriptive design using two open-ended questions to enhance data collection. A total of 120 college students were recruited to participate in this study. The research questions were: “What are college students’ perceptions of influenza vaccination?” and “What are college students’ perceptions of childhood immunizations?” The health belief model was used to guide the study. Results/Conclusion: Survey results showed that many students in a Christian college believe immunization is effective and plan to immunize their future children. However, a few students stated a desire to learn more about immunization.